Antitumor activity of potent pyruvate dehydrogenase kinase 4 inhibitors from plants in pancreatic cancer. Issue 10 (20th May 2019) - Tambe, Yukihiro; Terado, Tokio; Kim, Chul Jang; Mukaisho, Ken‐ichi; Yoshida, Saori; Sugihara, Hiroyuki; Tanaka, Hiroyuki; Chida, Junji; Kido, Hiroshi; Yamaji, Kenzaburo; Yamamoto, Tsuyoshi; Nakano, Hirofumi; et al.
Abstract: Phosphorylation of pyruvate dehydrogenase by pyruvate dehydrogenase kinase 4 (PDK4) 4 inhibits its ability to induce a glycolytic shift. PDK4 expression is frequently upregulated in various cancer tissues, with its elevation being critical for the induction of the Warburg effect. PDK4 is an attractive target for cancer therapy given its effect on shifting glucose metabolism. Previous research has highlighted the necessity of identifying a potent compound to suppress PDK4 activity at the submicromolar concentrations. Here we identified natural diterpene quinones (KIS compounds) that inhibit PDK4 at low micromolar concentrations. KIS37 (cryptotanshinone) inhibited anchorage‐independent growth in three‐dimensional spheroid and soft agar colony formation assays of KRAS‐activated human pancreatic (MIAPaCa‐2 and Panc‐1) and colorectal (DLD‐1 and HCT116) cancer cell lines. KIS37 also suppressed KRAS protein expression in such cell lines. Furthermore, KIS37 suppressed phosphorylation of Rb protein and cyclin D1 protein expression via the PI3K‐Akt–mTOR signaling pathway under nonadherent culture conditions and suppressed the expression of cancer stem cell markers CD44, EpCAM, and ALDH1A1 in MIAPaCa‐2 cells. KIS37 also suppressed pancreatic cancer cell growth in both subcutaneous xenograft and orthotopic pancreatic tumor models in nude mice at 40 mg/kg (intraperitoneal dose) without any evident toxicity. Reduced ALDH1A1 expression was observed in KIS37‐treated pancreatic tumors, suggesting that cancer cell stemness was also suppressed in the orthotopic tumor model. The aforementioned results indicate that KIS37 administration is a novel therapeutic strategy for targeting PDK4 in KRAS‐activated intractable human pancreatic cancer.